Odporność świerka na hubę korzeni - Chomicz-Zegar, Elżbieta (Leśne Prace Badawcze, 2012)
Heterobasidion spp. are a major pathogen causing root rot in coniferous trees, leading to great economic losses in forest management. Norway spruce ( Picea abies ) exhibits variable resistance to root rot, but the basis for variation in its resistance is not well understood. Ecological and genetic components were distinguished both to resistance to the initial infection and to its spread. Resistance was assessed using several techniques, including the artificial inoculation of living tree trunks or derived tissue cultures, the inoculation of spruce heartwood in laboratory condition, artificial inoculation of neighbouring stumps in plantation and field resistance trials. The results of previuous experiments were overviewed and discussed.